Webinar: Error 404, farmer not found. Why agricultural information services must consider how smallholders use their phones - Steinke, Jonathan; Ortiz-Crespo, Berta (2024)
This webinar presented the working paper "error 404 - farmer not found" which explores the behavioral barriers that limit farmers' use of mobile phone-based services. Drawing from the experiences of 15 CGIAR researchers from 12 different projects in 10 countries, we describe 18 unique barriers on how farmers use their phones within their specific contexts. The webinar counted with experts from different fields who discussed the issues that can be found when deploying phone based services for farmers and how they can be overcomed, pointing out solutions such as AI, gamification, sustainable business models, relying on local experts, or applying mix methods for in-depth user research.